Epidemiology of vertebral fractures in pediatric and adolescent patients - Dominik Saul; Klaus Dresing (MDPI AG, 2018)
Spinal injuries in children and adolescents are rare injuries, but consequences for the growing skeleton can be devastating. Knowledge of accident causes, clinical symptoms and diagnostics should be part of every trauma department treating the sepatients. We retrospectively analyzed patients with radiographically proven vertebral fractures of the spine. After clinical examination and tentative diagnosis the fractures and injuries were proven with conventional X-ray, computed tomography(CT) scans or magnetic resonance imaging (MRI). The study included 890 fractures in 546 patients with an average age of 12.8±6.2 (6.6-19.4) years. Females had anaverage age of 13.7±6.3 (7.4-20.0) years, whereas males were on average 12.0 (6.0-18.0) years old. Fall from height (58%) wasthe main cause of accident and the most common region of fracture was the thoracolumbar spine with a shift towards the thoracic spine the more fractures occurred. Merely 3.7% of all patients required operative treatment. If a vertebral fracture is found in children and adolescents, it is highly recommended to exclude synchronous additional spine fractures in other levels; prevention should concentrate on fall and traffic accidents.